Computational and experimental investigation of bone cell response to mechanical stimuli - McGarry, James Gerard (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2006)
The importance of mechanical loading in maintaining bone quality is well illustrated by the drastic effects of its absence in, for example, microgravity, cast immobilisation or paraplegia. The mechanisms underlying adaptation of bone to mechanical loading occur on the cellular level. However, it remains unclear how a mechanical stimulus is detected by an osteoblast or an osteocyte to subsequently influence the signalling pathways that would lead to important signalling responses such as nitric oxide (NO) or prostaglandin E2 (PGE2) release.
Keywords: Mechanical Engineering, Ph.D.; Ph.D. Trinity College Dublin